A GESTÃO AMBIENTAL E O PROCESSO DA EDUCAÇÃO AMBIENTAL NO PARQUE ESTADUAL MATAS DO SEGREDO EM CAMPO GRANDE/MS - Kássia Aparecida Pereira de Oliveira (2025)
In the 1970s, following the Stockholm Conference, the world’s nations began to recognize the importance of global biodiversity as a crucial factor in the health of the planet. Therefore, a global commitment was made to keep part of the biomes preserved so that all generations can enjoy their natural beauty and the benefits of having contact with the natural environment. For this purpose, we have Conservation Units (CUs), which are the main way to preserve biomes and biodiversity. In order to better explore the potential of Conservation Units, as an instrument of conservation and environmental preservation, we focused our study on analyzing, discussing, and reflecting on the information collected regarding how Environmental Education (EE) is disseminated in the Parque Estadual Matas do Segredo (Matas do Segredo State Park, PEMS). In an attempt to achieve our objectives, we divided this work into two sections in scientific article format. The first section, we discuss the actions and motivation of the State in promoting EE within the scope of PEMS. The first section revealed that the dissemination of EE happens through the Projeto Florestinha, which has a preservationist bias. In the second section, we address issues relating to Environmental Management and its importance in the dissemination of Environmental Education (EE) in the aforementioned UC. To address this point in the research, we analyzed the minutes of the PEMS Advisory Council, referring to the 2019-2021 and 2021-2023 biennia. In this way, we understand some strategies used in the management of PEMS, to increase the community's knowledge regarding the existence of the park, such as the need to prepare the Public Use Plan and review the Management Plan. This analysis revealed the occurrence of “Um Dia no Parque,” a one-off event that happens once a year and serves to bring the community closer to the UCs. It was evident in this section that the current EE activities developed in the park are important, but the CEE can deepen discussions on environmental management, considering social justice and the need for social transformation. We understand that integrating scientific research, environmental management, and environmental education, from the perspective of CEE, will allow PEMS to become a sustainable educational space capable of generating more effective and lasting results in protecting the environment.